Strategi Internalisasi Nilai-Nilai Agama Islam dalam Meningkatkan Religiusitas Siswa di SMA Islam Al-Fattah Pecalongan Bondowoso - Nor Alim Kilmi; Muhammad Munif (Social Science Academic, 2026)
This article aims to analyze the strategy of internalizing Islamic religious values ​​in increasing student religiosity at Al-Fattah Islamic High School in Pecalongan, Bondowoso. The research used a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The research findings show that the internalization of Islamic religious values ​​occurs through four main strategies: habituation, role modeling, motivation, and reward and punishment. Habituation is realized through congregational prayer, group prayer, the habit of greeting, and routine religious activities that foster discipline and religious awareness in students. Exemplary behavior is evident in teacher behavior in worship, polite speech, discipline, and consistency between words and actions. Motivation is provided through advice, religious direction, spiritual strengthening, and a personal approach to foster students' internal awareness in practicing Islamic teachings. Rewards and punishments are applied educationally and proportionally to strengthen positive behavior, foster violations, and foster responsibility and self-control. This article emphasizes that student religiosity is more easily formed when religious values ​​are presented in an integrated manner through a religious school culture.